Expected Sonographic Appearance of the Spleen in Children and Young Adults With Sickle Cell Disease: An Update. (27th June 2016) - Gale, Heather I.; Bobbitt, Christopher A.; Setty, Bindu N.; Sprinz, Philippa G.; Doros, Gheorghe; Williams, Don D.; Morrison, Trevor C.; Kalajian, Tyler A.; Tu, Powen; Mundluru, Shankar N.; Castro-Aragon, Ilse
Abstract : Objectives: : To update the imaging literature regarding spleen appearances in young patients with sickle cell disease (SCD). Methods: We conducted a retrospective study and included 112 patients age 0 to 21 years with SCD who had at least 1 abdominal sonogram at our institution between 1999 and 2011. Radiologic findings were compared between risk groups by χ 2 analysis. Findings were correlated with other imaging modalities when available. Results: In our cohort, 35.7% of patients had autosplenectomy, and 8.0% had undergone surgical splenectomy. Only 5.0% of individuals age 0 to 5 years had autosplenectomy. In those who had not undergone surgical splenectomy or autosplenectomy, 76.2% had echogenic spleens, heterogeneous‐appearing spleens, or both, and patients with the homozygous sickle cell anemia (HbSS) genotype were more likely to have an abnormal spleen echo texture. Patients treated with transfusions had echogenic spleens and had a higher frequency of splenic regeneration nodules. Most patients (80%) with splenomegaly did not require surgical splenectomy after 5.7 years of follow‐up. Conclusions: Twenty years ago, children with HbSS SCD were expected to have autosplenectomy by age 5 years. There have been changes in the radiologic appearance of the spleen in patients with SDC, likely due to improved supportive care and the use of acute and chronic transfusion therapy. We found that autosplenectomy is rare by age 5 years, and during childhood and adolescence, the spleen typically appears echogenic, heterogeneous, or both, depending on disease severity.